2003
DOI: 10.1074/jbc.m308881200
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping Specificities of the Mitochondrial Cytochrome c and c1 Heme Lyases

Abstract: Heme attachment to the apoforms of fungal mitochondrial cytochrome c and c 1 requires the activity of cytochrome c and c 1 heme lyases (CCHL and CC 1 HL), which are enzymes with distinct substrate specificity. However, the presence of a single heme lyase in higher eukaryotes is suggestive of broader substrate specificity. Here, we demonstrate that yeast CCHL is active toward the non-cognate substrate apocytochrome c 1 , i.e. CCHL promotes low levels of apocytochrome c 1 conversion to its holoform in the absenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
119
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(126 citation statements)
references
References 82 publications
(83 reference statements)
5
119
0
2
Order By: Relevance
“…Furthermore, the measured decrease in COX enzyme activities in the intact ⌬su g mitochondria would also argue that the effect in the cytochrome bc 1 -COX supercomplex in the absence of Su g (or Su e) is not because of an in vitro detergent artifact. Finally, Western blotting analysis of ⌬su g and ⌬su e mitochondria has indicated that the steady state levels of cytochrome c are markedly increased in the absence of Su g or Su e. An increased expression level of cytochrome c has been observed previously in other COX-mutant yeast strains (53,54), further supporting the conclusion here that the COX activity is compromised in the absence of subunits e and g of the F 1 F 0 -ATP synthase.…”
Section: Discussionsupporting
confidence: 71%
“…Furthermore, the measured decrease in COX enzyme activities in the intact ⌬su g mitochondria would also argue that the effect in the cytochrome bc 1 -COX supercomplex in the absence of Su g (or Su e) is not because of an in vitro detergent artifact. Finally, Western blotting analysis of ⌬su g and ⌬su e mitochondria has indicated that the steady state levels of cytochrome c are markedly increased in the absence of Su g or Su e. An increased expression level of cytochrome c has been observed previously in other COX-mutant yeast strains (53,54), further supporting the conclusion here that the COX activity is compromised in the absence of subunits e and g of the F 1 F 0 -ATP synthase.…”
Section: Discussionsupporting
confidence: 71%
“…It would be interesting to investigate whether ERV1 could catalyze the formation of a disulfide bond in apocytochromes, thus making the reducing activity of proteins such as CCMH necessary. Indeed, Cyc2p, a flavoprotein was recently shown to interact with system III CCHL and proposed to be involved in the redox chemistry of the heme lyase reaction in yeast mitochondria (38). Further investigations of the function of CCMH might give clues toward the understanding of the yet unknown mechanisms controlling the intermembrane space redox state in mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, defects in the mitochondrial respiratory chain lead to severe cardiomyopathies (diseases characterized by deterioration of myocardial function), since cardiomyocytes are exquisitely sensitive to changes in metabolic conditions (69). In mammals, holocytochrome c synthase, which is encoded by the gene Hccs on the X chromosome, converts cytochrome c and cytochrome c1 to their active forms by attaching a heme moiety (70). Drenckhahn and colleagues engineered a cardiac-specific Hccs knockout (68).…”
Section: Studies Of Regeneration In the Embryonic Mammalian Heartmentioning
confidence: 99%